Wireless Mobile Communication and Healthcare Second International ICST Conference, MobiHealth 2011, Kos Island, Greece, October 5-7, 2011. Revised Selected Papers - Nikita, Konstantina S.; Lin, James C.; Fotiadis, Dimitrios I.; Arredondo Waldmeyer, Maria-Teresa.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the Second International ICST Conference on Wireless Mobile Communication and Healthcare, MobiHealth 2011, held on Kos Island, Greece, in October 2011. The 60 revised full papers presented were carefully reviewed and selected from more than 80 submissions. The papers are organized in 10 sessions and two workshops with topics covering intrabody communications, chronic disease monitoring and management, ambient assistive technologies, implantable and wearable sensors, emergency and disaster applications.
Keywords: Computer science; Medical records -- Data processing; Computer Communication Networks; Data mining; Computer simulation; Computer vision; Bioinformatics; Computer Science; Computational Biology/Bioinformatics.; Health Informatics; Computer Communication Networks; Data Mining and Knowledge Discovery; Simulation and Modeling; Image Processing and Computer Vision